Socio-cultural factors of trust in East Asian business networks - Shatun, Anna (Актуальні питання економічних наук, 2025)
The relevance of the study is determined by the growing importance of trust as a key mechanism for ensuring the stability and effectiveness of business interactions in the economies of East Asian countries amid globalization, digitalization, and intensified cross-border cooperation. The purpose of the article is to identify and systematize the socio-cultural factors that shape trust in East Asian business networks, and to analyze the mechanisms of interaction between traditional and modern forms of trust in contemporary economic conditions. Methods: analysis of scientific literature to examine the current state of research on the problem; generalization and systematization to present the research results. The research results reveal the multidimensional nature of trust as a socially embedded phenomenon that integrates ethical, relational, and institutional components. It is substantiated that Confucian value orientations, in particular moral obligation, reciprocity, and role-based responsibility, continue to exert a significant influence on inter-firm trust, shaping expectations of legitimate and reliable behavior beyond formal contractual frameworks. It is established that interpersonal ties, kinship relations, and informal social connections function as effective mechanisms for the transmission and reinforcement of trust within business networks, reducing uncertainty and fostering long-term cooperation. It is noted that under the influence of globalization, trust increasingly takes hybrid forms that combine culturally conditioned relational trust with formalized institutional guarantees and digital trust mechanisms. The results also show that digital platforms and transnational networks do not eliminate traditional trust practices but rather reconfigure them by embedding personal and reputational trust into technologically mediated systems of coordination and control. It is substantiated that such hybridization enhances the adaptive capacity of East Asian business networks, enabling them to maintain internal cohesion while simultaneously expanding their participation in global economic processes. Conclusions. It is emphasized that trust in East Asian business networks should be understood as a complex and continuously evolving construct shaped by socio-cultural continuity and structural transformations. It is established that the sustainability of these networks depends on their ability to integrate traditional ethical norms and interpersonal relationships with modern institutional and digital forms of regulation. This integrative model of trust formation provides East Asian businesses with a competitive advantage by supporting resilience, flexibility, and long-term strategic cooperation in volatile global markets.